2017
DOI: 10.1111/bph.13990
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine is a potent pulmonary vasodilator that attenuates hypoxia‐induced pulmonary hypertension

Abstract: *These authors contributed equally to this work. BACKGROUND AND PURPOSESustained pulmonary vasoconstriction and excessive pulmonary vascular remodelling are two major causes of elevated pulmonary vascular resistance in patients with pulmonary arterial hypertension. The purpose of this study was to investigate whether chloroquine induced relaxation in the pulmonary artery (PA) and attenuates hypoxia-induced pulmonary hypertension (HPH). EXPERIMENTAL APPROACHIsometric tension was measured in rat PA rings pre-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 67 publications
(91 reference statements)
3
42
0
Order By: Relevance
“…In concordance with these findings, several autophagy inhibitors have been tested in animal models and were able to attenuate PAH development. Lysosomal inhibitors, chloroquine and hydroxychloroquine, which inhibit autophagy by preventing autophagosome maturation, were reported to diminish proliferation of SMC and reduce PAH pathogenesis in monocrotaline-treated rats [ 320 ] and hypoxia-exposed mice [ 324 ]. Zhang and colleagues reported hypoxia-induced proliferation of PASMC can be reversed by another inhibitor of autophagy, 3-MA [ 323 ].…”
Section: Autophagy and Ros In Pulmonary Diseasesmentioning
confidence: 99%
“…In concordance with these findings, several autophagy inhibitors have been tested in animal models and were able to attenuate PAH development. Lysosomal inhibitors, chloroquine and hydroxychloroquine, which inhibit autophagy by preventing autophagosome maturation, were reported to diminish proliferation of SMC and reduce PAH pathogenesis in monocrotaline-treated rats [ 320 ] and hypoxia-exposed mice [ 324 ]. Zhang and colleagues reported hypoxia-induced proliferation of PASMC can be reversed by another inhibitor of autophagy, 3-MA [ 323 ].…”
Section: Autophagy and Ros In Pulmonary Diseasesmentioning
confidence: 99%
“…Since autophagy is necessary in cell homeostasis, cardiac QT elongation [140,141] and anaemia [142] are common CQ/HCQ side effects related to autophagy inhibition and need to be used with care. Additionally, CQ induces autophagy-independent effects, like Golgi disorganization [143] and pulmonary vasodilation [144], contributing to its controversial clinical activity. To avoid these effects and to obtain a limitation of autophagy in order to reduce cytokine activation, IL-6R mAb has been found effective in different settings [145,146].…”
Section: Autophagy Immunity and Virus Infectionmentioning
confidence: 99%
“…Sai et al () demonstrated that chloroquine induces vasodilation in rat aorta at high concentration (>100 μmol·L −1 ) via inhibiting voltage‐dependent L‐type Ca 2+ channel (VDCC). We have also found that pretreatment with chloroquine (200 μmol·L −1 ) attenuates vascular contraction in mouse pulmonary artery through inhibition of VDCC in smooth muscle cells (SMCs; Wu et al, ). Pestana et al () show that chloroquine relaxes vessels in a dose‐dependent manner by increasing NO production in rat aorta.…”
Section: Introductionmentioning
confidence: 80%
“…The vascular response to the same agonist is not always the same among different organs and branches of vessels. Although there are several studies investigating the effect of chloroquine on vascular response (Manson et al, ; Pestana et al, ; Sai et al, ; Wu et al, ), there is no report so far that examines the effect of chloroquine on vasodilation in CAs isolated from healthy and diabetic mice. Muscarinic agonist (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation